Effects of Vitamin D on Blood Pressure and Cardiovascular Risk Factors: A Randomized Controlled Trial. Issue 6 (June 2015) - Pilz, Stefan; Gaksch, Martin; Kienreich, Katharina; Grübler, Martin; Verheyen, Nicolas; Fahrleitner-Pammer, Astrid; Treiber, Gerlies; Drechsler, Christiane; ó Hartaigh, Bríain; Obermayer-Pietsch, Barbara; Schwetz, Verena; Aberer, Felix; et al.
Abstract : Vitamin D deficiency is a risk factor for arterial hypertension, but randomized controlled trials showed mixed effects of vitamin D supplementation on blood pressure (BP). We aimed to evaluate whether vitamin D supplementation affects 24-hour systolic ambulatory BP monitoring values and cardiovascular risk factors. The Styrian Vitamin D Hypertension Trial is a single-center, double-blind, placebo-controlled study conducted from June 2011 to August 2014 at the endocrine outpatient clinic of the Medical University of Graz, Austria. We enrolled 200 study participants with arterial hypertension and 25-hydroxyvitamin D levels below 30 ng/mL. Study participants were randomized to receive either 2800 IU of vitamin D3 per day as oily drops (n=100) or placebo (n=100) for 8 weeks. Primary outcome measure was 24-hour systolic BP. Secondary outcome measures were 24-hour diastolic BP, N-terminal-pro-B-type natriuretic peptide, QTc interval, renin, aldosterone, 24-hour urinary albumin excretion, homeostasis model assessment-insulin resistance, triglycerides, high-density lipoprotein cholesterol, and pulse wave velocity. A total of 188 participants (mean [SD] age, 60.1 [11.3] years; 47% women; 25-hydroxyvitamin D, 21.2 [5.6] ng/mL) completed the trial. The mean treatment effect (95% confidence interval) for 24-hour systolic BP was −0.4 (−2.8 to 1.9) mm Hg ( P =0.712). Triglycerides increased significantly (mean change [95% confidence interval], 17 [1–33] mg/dL; P =0.013), but no further significant effects were observed for secondary outcomes. Vitamin D supplementation in hypertensive patients with low 25-hydroxyvitamin D has no significant effect on BP and several cardiovascular risk factors, but it was associated with a significant increase in triglycerides. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02136771. Abstract : Supplemental Digital Content is available in the text.